Locus Coeruleus Dysfunction in Transgenic Rats with Low Brain Angiotensinogen. (18th January 2016) - Ogier, Michael; Bricca, Giampiero; Bader, Michael; Bezin, Laurent
Summary: Aims: Transgenic TGR(ASrAOGEN)680 (TGR) rats with specific downregulation of glial angiotensinogen (AOGEN) synthesis develop cardiovascular deficits, anxiety, altered response to stress, and depression. Here, we evaluated whether these deficits are associated with alteration of the integrity of the noradrenergic system originating from locus coeruleus (LC) neurons. Methods: Adult TGR rats were compared to control Sprague Dawley rats in terms of the following: tissue levels of transcripts encoding noradrenergic markers, tissue tyrosine hydroxylase (TH) protein level, in vivo TH activity, density of TH‐containing fibers, behavioral response to novelty, locomotor activity, and polysomnography. Results: TH expression was increased in the LC of TGR rats compared to controls. In LC terminal fields, there was an increase in density of TH‐containing fibers in TGR rats that was associated with an elevation of in vivo TH activity. TGR rats also displayed locomotor hyperactivity in response to novelty. Moreover, polysomnographic studies indicated that daily paradoxical sleep duration was increased in TGR rats and that the paradoxical sleep rebound triggered by total sleep deprivation was blunted in these rats. Conclusions: Altogether, these results suggest that disruption of astroglial AOGEN synthesis leads to cardiovascular, cognitive, behavioral, and sleep disorders that might be partly due to LC dysfunction.